Towards effective healthcare information SMS model - Mwashuma, Elizabeth Wanjala; Chepken, Chepken Christopher (Journal of Health Informatics in Africa, 2018)
Problem: The healthcare sector uses SMS to disseminate healthcare information to a large population of people. Maternal and post-natal healthcare information is widely delivered through SMS messaging. Evidence of a structure used when sending the healthcare information via SMS, ensuring that the message received is effective, remains very limited.Objective: This paper presents a study which was aimed at proposing a model, presenting salient factors, which can be used to effectively send healthcare information via SMS.Methods: A total of 80 people were initially recruited. However, 63 out of the 80 people, all residing in Nairobi participated in this study. 52 respondents were interviewed over the phone using semi-structured scripts, six of them participated in a focus group discussion carried out at a Hospital in the Eastern part of Nairobi. Five respondents responded to questionnaires issued to them.Results: Through review of literature and data analysis, five factors emerged which influence effectiveness of healthcare messages sent via SMS. The factors include: the time of day in which respondent has most access of their phone, the day of the week most preferred to receive the SMS, frequency of receiving the healthcare messages, topics of interest to the receiver and preferred language.Conclusions: This study shows that to ensure healthcare messages sent over SMS are effective, it is important that information is sent to the recipient subject to their availability and preferences. Healthcare institutions need to consider these factors when sending healthcare information, to ensure information sent is relevant and convenient to the receiver thus resulting in expected behavior change.The model can be adopted in other sectors which rely on SMS to send information to its beneficiaries.  KeywordsSMS, mhealth, TotoHealth, MNCHACM Classification KeywordsH.5.m. Information interfaces and presentation (e.g., HCI): Miscellaneous